1995
DOI: 10.1164/ajrccm.152.2.7633718
|View full text |Cite
|
Sign up to set email alerts
|

Increased degranulation of eosinophil and neutrophil granulocytes in cystic fibrosis.

Abstract: Increased serum and sputum concentrations of eosinophil cationic protein (ECP) and of neutrophil myeloperoxidase (MPO) have been described in patients with cystic fibrosis. Because numbers of eosinophils are normal in both peripheral blood and in the lung of patients with cystic fibrosis, we investigated whether eosinophils presented with an increased propensity to release their granule proteins. We investigated 20 patients with cystic fibrosis, 19 individuals with bronchial asthma, and 21 healthy nonatopic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
3
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 15 publications
5
77
3
3
Order By: Relevance
“…This may be due to CF neutrophils having less stored elatase due to their higher spontaneous rate of release compared to control neutrophils. Another study found that the neutrophils from CF patients released granule proteins, such as MPO, in an enhanced manner compared to normals [13], yet the data presented here suggest that CF neutrophils release less granule products than normals. The reason for this discrepancy could be that MPO could be released quickly and in greater amounts than elastase.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This may be due to CF neutrophils having less stored elatase due to their higher spontaneous rate of release compared to control neutrophils. Another study found that the neutrophils from CF patients released granule proteins, such as MPO, in an enhanced manner compared to normals [13], yet the data presented here suggest that CF neutrophils release less granule products than normals. The reason for this discrepancy could be that MPO could be released quickly and in greater amounts than elastase.…”
Section: Discussioncontrasting
confidence: 65%
“…For example, neutrophils and eosinophils isolated from CF patients have been shown to have an altered arachidonic acid turnover [12], and an increased release of myeloperoxidase (MPO), eosinophil cationic protein (ECP), and eosinophil protein X (EPX) [13]. In addition, isolated peripheral neutrophils from CF patients generated higher levels of elastase when exposed to stimuli such as IL-8 and TNFa compared to neutrophils isolated from controls [14].…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies suggest that the changes in inflammation caused by CF may be an inherent feature of immune cells involved in the inflammatory process as well as lung epithelial and submucosal gland serous cells. [25][26][27][28][29][30] Finally, gene expression studies in the CFTR knockout mice have clearly indicated an upregulation of many genes, including IL-4, 18 which likely forms the basis for the observations in the current study. In mice, total serum IgE and IgG1 are definitely correlated with IL-4 production and a Th2-predominant response, so that our findings should have been predicted based on those studies.…”
Section: Discussionmentioning
confidence: 73%
“…There is evidence from clinical studies that an exaggerated recruitment and activation of neutrophilic granulocytes in the airways is linked to the clinical course of several inflammatory diseases in the airways and lungs, such as asthma (1)(2)(3)(4)(5)(6)82), nonspecific bronchial hyperreactivity (BHR) (7), chronic bronchitis (3,(8)(9)(10), chronic obstructive pulmonary disease (COPD) (3,(11)(12)(13), cystic fibrosis (14)(15)(16)(17), and acute respiratory distress syndrome (18)(19)(20). The referred evidence has been gathered analysing cellular contents in bronchial tissue, in bronchoalveolar lavage (BAL) fluid, in bronchial biopsies, in induced sputum and in peripheral blood.…”
Section: Neutrophilic Airway Inflammationmentioning
confidence: 99%